Unusual reversible twinning modes and giant superelastic strains in FeNiCoAlNb single crystals. (1st July 2016) - Chumlyakov, Y.I.; Kireeva, I.V.; Kutz, O.A.; Turabi, A.S.; Karaca, H.E.; Karaman, I.
Abstract: The superelastic response of the Fe41 Ni28 Co17 Al11.5 Nb2.5 (at. %) single crystals oriented along the [001] direction was investigated in tension at various temperatures after aging at 973 K for 0.5 h. The aging treatment led to the formation of ordered γ' particles with particle sizes of less than 3 nm. Abnormally large reversible strain of up to 15.3% was observed at 77 K, the highest ever reported for an iron-based shape memory alloys. It has been revealed that this giant superelastic strain, significantly higher than the theoretical transformation strain, is associated with γ-α' martensitic transformation and elastic mechanical twinning of < 011 >110 type. Graphical abstract: